2020
DOI: 10.1186/s13071-020-04290-0
|View full text |Cite
|
Sign up to set email alerts
|

Clinical helminthiases in Thailand border regions show elevated prevalence levels using qPCR diagnostics combined with traditional microscopic methods

Abstract: Background: Under-regulated national borders in Southeast Asia represent potential regions for enhanced parasitic helminth transmission and present barriers to helminthiasis disease control. Methods: Three Thailand border regions close to Myanmar, Laos and Cambodia were surveyed for clinical parasitic helminth disease. In-field microscopy was performed on stools from 567 individuals. Sub-samples were transported to Bangkok for molecular analysis comprising three multiplex qPCR assays. Results: The overall helm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
30
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 12 publications
(33 citation statements)
references
References 29 publications
1
30
0
Order By: Relevance
“…Southeast Asia carries the STH infection burden where almost one-third of global helminthiases are recorded [ 4 ]. Strongyloides stercoralis , Opisthorchis viverrini , hookworm, Ascaris and Trichuris are major endemic species in Northern Thailand [ 5 , 6 ]. Many of these helminth infections have a systemic impact on human health via interactions with the host immune response [ 7 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Southeast Asia carries the STH infection burden where almost one-third of global helminthiases are recorded [ 4 ]. Strongyloides stercoralis , Opisthorchis viverrini , hookworm, Ascaris and Trichuris are major endemic species in Northern Thailand [ 5 , 6 ]. Many of these helminth infections have a systemic impact on human health via interactions with the host immune response [ 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…In a recent study, we demonstrated more accurate helminth infection prevalence data in a Southeast Asia cohort study using molecular diagnostics [ 6 ]. Here, using this diagnostic information, we present the impact that active helminth infections have on the host faecal and saliva microbiomes.…”
Section: Introductionmentioning
confidence: 99%
“…Tha Song Yang District is an endemic area for the IPIs, including amoebic dysentery and helminthic infections (Adisakwattana et al, 2020). However, their actual prevalence, risk factors, and specific intervention were under-reported.…”
Section: Discussionmentioning
confidence: 99%
“…Tha Song Yang District, Tak Province at the Thai-Myanmar border, was the highest contributor of the IPI cases, including bloody diarrhea or amoebic dysentery caused by Entamoeba histolytica (Bureau of Epidemiology, 2019). Prevalence of intestinal helminthic infection of Tha Song Yang was 18%, and predominantly by Opisthorchis viverrini (18.34%), hookworm (6.88%), Ascaris lumbricoides (2.29%) and Trichuris trichiura (1.76%) (Adisakwattana et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…To detect and quantify helminth infections, Kato-Katz was performed. A thick smear was prepared from the fresh stool according to the manufacturer's instructions (Kato-Katz kit, Mahidol University, Thailand) [40]. Infection intensity was stratified into light, moderate or heavy according to WHO cut-offs [41].…”
Section: Fecal Sample Preparation and Analysismentioning
confidence: 99%